AKTIVITAS ANTIBAKTERI FRAKSINASI EKSTRAK DAUN ASAM JAWA (Tamarindus indica L.) (Tamarindus indica L.) TERHADAP BAKTERI Salmonella thyphi DAN Escherichia coli DENGAN METODE KLT-BIOAUTOGRAFI - Rusli, Rusli; Faradila, Aulia; Kosman, Rachmat (PHARMACY UMI JOURNAL SYSTEM, 2023)
Tropical infectious diseases are often caused by viruses, bacteria, fungi or even parasites. Indonesian people use medical plants to treats diseases. One of them is tamarind leaves which have the ability as an antibacterial. The purpose of this study was to determine the antibacterial activity of the fractionated extract of tamarind leaves (Tamarindus indica L.) against Salmonella thyphi and Escherichia coli. Tamarind leaf simplicial was extracted using the maceration method and evaporated with a rotary evaporator to obtain thick extract. Then fractionated using n-hexane and ethyl acetate and evaporated again with a rotary evaporator. After that, ethyl acetate fraction of tamarind leaves (Tamarindus indica L.) was used for antibacterial screening test with a concentration of 0,1% and 0,5%. Then, the TLC-Bioautography test was carried out and followed by the identification of chemical components. The results of the screening test of the ethyl acetate fraction of tamarind leaves (Tamarindus indica L.) showed antibacterial activity against Salmonella thyphi and Escherichia coli. TLC-Bioautography test result showed that it was active on Salmonella thyphi and Escherichia coli with an Rf value of 0,81. Then the results of the identification of the chemical component of the ethyl acetate fraction of tamarind leaves (Tamarindus indica L.) were positive for alkaloid and taninns. Based on this study, tamarind leaves have the potential as an antibacterial.